Impact of forest degradation on Palawan endemic birds its implication to avifaunal conservation - Bernardo Alejandro A., Jr.; Regoniel, Patrick A. (2015)
This study determined the effect of habitat alteration on species richness and abundance of Palawan endemic birds and described their conservation status relative to forest degradation. An avifaunal survey was conducted from July to September 2011 in Aborlan, Palawan, Philippines. Using a standard point count method the species richness and abundance of endemic bird species and endemic bird races from selected degraded forests sites such as residual forest and abandoned swidden farm were recorded and compared to adjacent primary forest. The species richness and abundance of forest dwelling birds decline with forest degradation. The severity of impact takes a high toll on the endemic bird soecies and endemic races.
Keywords: Endemic birds; Forest degradation; Upland ecosystem; Palawan birds